Ancient Mitogenomes Reveal the Origins and Genetic Structure of the Neolithic Shimao Population in Northern China - Xue, Jiayang; Wang, Wenjun; Shao, Jing; Dai, Xiangming; Sun, Zhouyong; Gardner, Jacob D.; Chen, Liang; Guo, Xiaoning; Di, Nan; Pei, Xuesong; Wu, Xiaohong; Zhang, Ganyu; et al. (Frontiers in Genetics, 2022)
Shimao City is considered an important political and religious center during the Late Neolithic Longshan period of the Middle Yellow River basin. The genetic history and population dynamics among the Shimao and other ancient populations, especially the Taosi-related populations, remain unknown. Here, we sequenced 172 complete mitochondrial genomes, ranging from the Yangshao to Longshan period, from individuals related to the Shimao culture in northern Shaanxi Province and Taosi culture in southern Shanxi Province, Middle Yellow River basin. Our results show that the populations inhabiting Shimao City had close genetic connections with an earlier population in the Middle Neolithic Yangshao period of northern Shaanxi Province, revealing a mostly local origin for the Shimao Society. In addition, among the populations in other regions of the Yellow River basin, the Shimao-related populations had the closest maternal affinity with the contemporaneous Taosi populations from the Longshan period. The Shimao-related populations also shared more affinity with present-day northern Han populations than with the minorities and southern Han in China. Our study provides a new perspective on the genetic origins and structure of the Shimao people and the population dynamics in the Middle Yellow River basin during the Neolithic period.